Analisis Penilaian Stakeholders Terhadap Pelaksanaan Praktik Kerja Lapangan (PKL) Mahasiswa Program Studi (Prodi) Manajemen Pendidikan Islam - Siti Julaiha; Marniati Kadir (LP2M UIN Sultan Aji Muhammad Idris Samarinda, 2013)
The research goal is to find out how the stakeholders evaluation toward the implementation of the PKL (Field Work Practice) of MPI students of STAIN Samarinda. The research is a descriptive qualitative research. The data sources are stakeholders evaluation that consist of headmaster, chief of Administration (TU) and tutor. Data is obtained by document and interview. The data collection technique that is used is analysis model of Miles & Huberman that is done by four activities, namely: data collecting, data reduction, data presentation, and summary drawing or verification. The research result shows that the stakeholders evaluation towards the PKL implementation of MPI students of STAIN Samarinda includes three evaluation aspects, namely evaluation in education and teaching aspect, school administration aspect, also public service aspect. Stakeholders evaluation towards thePKL of MPI students of STAIN Samarinda for the aspects of education and teaching also school administration are dominant with a good qualification, means that has mastered or there is a suitability between planning with teaching and administrating implementation. While the public service can be concluded that the implementation of MPI students PKL of STAIN Samarinda is dominant to get the stakeholders evaluation with an excellent qualification, means that in the social relation of society and the communication is already excellent with the school people.